Analysis of Factors Influencing Accounting Students in Choosing a Career as a Public Accountant - Kotte, Jeniwanti Carolina; Natalia, Desi; Kaloeti, Ade Kristianus (Invoice : Jurnal Ilmu Akuntansi, 2024)
This research aims to identify the factors influencing accounting students' career choices as public accountants, focusing on students from various universities in Yogyakarta. The study examines four key variables: financial rewards, professional training, work environment, and market considerations. Using a case study approach, data were collected through questionnaires and analyzed via logistic regression and classical assumption tests. The results indicate that financial rewards, professional training, and the work environment significantly influence students' decisions to pursue careers as public accountants. However, job market considerations do not have a significant effect. The findings emphasize that students place high importance on adequate compensation, professional development opportunities, and a conducive work environment when making career decisions. This research provides valuable insights into how universities can better support students in choosing relevant career paths and highlights the importance of aligning educational outcomes with industry expectations. Further, it underscores the need for ongoing professional training and development for accounting students to meet the demands of the profession. These results could serve as a guide for curriculum development and career advisory services in accounting education.